2006
DOI: 10.1002/dvdy.20979
|View full text |Cite
|
Sign up to set email alerts
|

Cell behaviors associated with somite segmentation and rotation in Xenopus laevis

Abstract: During vertebrate development the formation of somites is a critical step, as these structures will give rise to the vertebrae, muscle, and dermis. In Xenopus laevis, somitogenesis consists of the partitioning of the presomitic mesoderm into somites, which undergo a 90-degree rotation to become aligned parallel to the notochord. Using a membrane-targeted green fluorescent protein to visualize cell outlines, we examined the individual cell shape changes occurring during somitogenesis. We show that this process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 28 publications
3
52
1
Order By: Relevance
“…In Xenopus, a recent very detailed 3D confocal analysis of embryos confirms earlier explant observations (Wilson et al, 1989) that the expansion of short discrete fissures (Fig. 3B) acts to gently bisect the PSM to form a stable somite border (Afonin et al, 2006). Similarly, in zebrafish, cell rearrangements within a forming somite are minimal and a somite border forms when cells appear to gently detach from neighbors along a medio-to-lateral direction (Fig.…”
Section: Variations In Somite Border Formationsupporting
confidence: 82%
See 1 more Smart Citation
“…In Xenopus, a recent very detailed 3D confocal analysis of embryos confirms earlier explant observations (Wilson et al, 1989) that the expansion of short discrete fissures (Fig. 3B) acts to gently bisect the PSM to form a stable somite border (Afonin et al, 2006). Similarly, in zebrafish, cell rearrangements within a forming somite are minimal and a somite border forms when cells appear to gently detach from neighbors along a medio-to-lateral direction (Fig.…”
Section: Variations In Somite Border Formationsupporting
confidence: 82%
“…Interestingly, although Xenopus somites undergo a 90-degree rotation but do not epithelialize, time-lapse analyses showed that individual cells bend in a precise spatiotemporal manner that propagates in a dorsal-to-ventral direction (Afonin et al, 2006). In a similar manner, in analysis of histological sections from the chick PSM (Duband et al, 1987;Sato et al, 2002;Nakaya et al, 2004), the presumptive posterior border, including the dorsal, ventral, medial, and lateral sleeves of the new somite, appear epithelialized.…”
Section: Targeting Somite Epithelializationmentioning
confidence: 94%
“…Here, we show that the protein is detected from the onset of somitogenesis and is enriched at intersomitic junctions and at the notochord/somite boundaries. Somitogenesis requires the mediolateral elongation of presomitic cells, the formation of filopodia protrusions at the onset of rotation, the break of adhesive interactions with the ECM at the notochord/somite boundary, the bending of cells around the dorsoventral axis and finally the elongation and alignment of cells parallel to the notochord (Afonin et al, 2006). Dg is present during these events suggesting that Dg/ECM interactions might govern adhesive properties of cells during somitogenesis and muscle formation.…”
Section: Discussionmentioning
confidence: 99%
“…During gastrulation, presomitic cells of the paraxial mesoderm intercalate radially and mediolaterally, separate from the rest of the mesoderm, establish the notochord/somite boundary and finally form blocks of 7-9 cells width (Danker et al, 1992). In those blocks, cells change shape, lengthen along their mediolateral axis and narrow along their anteroposterior axis (Wilson et al, 1989;Afonin et al, 2006). At the onset of somitogenesis, the presomitic cells bend anteriorly and undergo a 90°rotation relative to the anteroposterior axis of the embryo to form mono-nucleate muscle cells that are aligned parallel to the notochord (Keller, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus embryos, two short, discrete fissures start from both the medial and lateral edges of the PSM and expand gradually towards the middle of the PSM to form a stable somite-PSM border (Afonin et al, 2006). In zebrafish embryos, cell rearrangements within forming somites are minimal and the forming-somite-PSM border develops when cells in the forming somite gently detach from their PSM neighbors, forming a medial notch which spreads laterally (Wood and Thorogood, 1994;Henry et al, 2000;Jiang et al, 2000).…”
Section: Introductionmentioning
confidence: 99%